Static Analysis of Gelatin-like Simulation Mass as a Subsoil in Scale Physical Modeling - Veronika Valašková; Jozef Vlček (Buildings)
The investigation of wave propagation in the geological environment is warranted, and will ultimately help to provide a better understanding of the response of subsoil to excitation. Frequently utilized physical modeling represents a simplification of the global natural system for the needs of the investigation of static and dynamic phenomena with regard to the time domain. The determination of appropriate model materials is probably the most important task for physical model creation. Considering that subsoil represents a crucial medium for wave propagation, an evaluation of suitable model materials was carried out. A plate load test with a circular plate is a non-destructive method for determining the static bearing capacities of soils and aggregates, which are usually expressed by the deformation modulus Edef,2 (MPa) and the static modulus of elasticity E (MPa). A lightweight deflectometer test was used to characterize the impact modulus of deformation Evd (MPa), which is determined based on the pressure under the load plate due to the impact load. A representative propagation of the load–settlement curve for the PLT and the acceleration–time curve for the hammer drop test were investigated. The calculated E values were found to be in the interval between 2.6 and 5.7 kPa, and depending on the load cycle, the values of E ranged from 2.6 to 3.1 kPa. The modulus E from the hammer drop test was significantly larger than the interval between 10.6 and 40.4 kPa. The values of the dynamic multiplier, as a ratio of the hammer drop value to the PLT value, of the modulus E ranged from 4.1 to 13.0. The output of the plate load testing was utilized for the calibration of the finite element method (FEM) numerical model. Both the physical and numerical models showed practically ideal linear behavior of the mass. However, the testing of gelatin-like materials is a complex process because of their viscoelastic nonlinear behavior.